Evaluation of Curcuma and Black Garlic Flour on Small Intestine Morphometrics, Carcass Weight, and Abdominal Fat of Broiler Chickens - W. Kuswandi; F. Ramadhan; Nurhayati; Nelwida; Berliana (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2024)
Curcuma flour and black garlic have potential benefits for chicken digestive health. A healthy digestive tract will help the process of absorbing feed more optimally. This research aimed to evaluate the potential of curcuma flour and black garlic in feed on small intestine morphometrics, carcass weight, and abdominal fat in broiler chickens. The study used 200 broiler chicken day-old chicks (DOC) randomly assigned to 5 treatments with 4 replications, including P0 = 100% commercial ratio (control), P1 = P0 + 2% black garlic, P2 = P1 plus 0.25% curcuma flour, P3 = P1 + 0.50% curcuma flour, and P4 = P1 + 0.75% curcuma flour. The study employed a completely randomized design (CRD), and the data were analyzed using analysis of variance (ANOVA). Significant differences between treatments were further tested using Duncan’s Multiple Range Test. The results showed that supplementation with Curcuma flour and black garlic in feed did not have a significant effect (P>0.05) on feed consumption, slaughter weight, small intestine morphometrics, carcass weight, carcass percentage, abdominal fat weight, and abdominal fat percentage. The results of this study indicate that the evaluation of Curcuma flour up to 0.75% and black garlic 2% in broiler chicken feed does not affect the activity of the small intestine, broiler carcass, and abdominal fat, as reflected in normal organ weights.